SENI SEBAGAI MEDIA DAKWAH PADA ANAK USIA DINI - Nur Rahmayani; Fatmawati Fatmawati; Mohammad Nur Ahsan (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2016)
This paper deals with the art as media of preaching in early childhood at the Early Childhood Education Institution of Kabelo Singgah-Singgani, Palu. The questions include (1) How does art become media of preaching in early childhood at this institution? (2) How is the implementation of art as media of preaching in early childhood at this institution? The result showed that, first, the art which is categorized as media of preaching is one which contains Islamic values. This Islamic art which is taught in this educational institution includes dances such as Kaili’s local dance called momonte, qasidah songs, Arabic calligraphy that contains Quranic verses, Hadith, and Islamic poetry. Various art instruments provided by this institution in supporting children’s activities comprise guitar, rebana (tambourine), kerincing (triangle), and sound system. The benefits of art gained by the children include giving joyful entertainment to children, introducing Islam through art, and habituating them with Islamic and local cultures. In addition, art will become a way to sharpen instinct and teach Islam with the tenderness of art.